Review on Trends of E-Commerce in India - Nitin kumar Jain (AG Volumes, 2021)
E - Commerce allows consumers to electronically exchange goods and services with no barriers of time or distance. It’s been projected that e-commerce will continue to grow at this pace, if not accelerate even more in the coming years. As more companies transfer parts of their operations to the Internet, the line between "traditional" and "electronic" trade will become more blurred. A high penetration of the internet and advanced electronic gadgets are driving rapid growth in India’s e-commerce sector. However, India’s recent e-commerce growth rate has lagged considerably below that of other industrialised nations. Convenience, time savings, and options are just a few of the benefits of electronic commerce. It’s simple to compare products and read customer feedback, thus Deals and coupons, expanding the base of clients more customers and more money, 24/7/365 extend the reach of your company, simplify recurring payments, and conduct transactions instantly. It also discusses some of the issues that need to be addressed.